Sense of Coherence, Social Support, Maternal-Fetal Attachment, and Antenatal Mental Health: A Survey of Expecting Mothers in Urban India - Pasricha, Moksha; Kochhar, Suhaavi; Shah, Ashumi; Bhatia, Avantika (Frontiers in Global Women's Health, 2021)
Introduction: Pregnancy is associated with psychological, physiological and social shifts, and can be a vulnerable time in a woman’s life. Despite a growing understanding of the importance of antenatal mental health, there is a paucity of research on psychosocial factors relevant to this phase, especially in developing countries. The aim of the present study was to investigate the associations of expecting mothers’ sense of coherence, perceived social support, and maternal-fetal attachment with mental health outcomes. Method: Participants (N = 122) were nulliparous expectant mothers residing in urban India. Cross-sectional data was collected using an online questionnaire. Results: Participant reports of perceived social support and sense of coherence were negatively correlated with symptoms of antenatal depression, while reports of maternal-fetal attachment, sense of coherence, and social support were positively associated with antenatal well-being. In a multilinear regression model, perceived social support and sense of coherence uniquely contributed to symptoms of antenatal depression, while maternal-fetal attachment and sense of coherence uniquely contributed to antenatal well-being. Discussion: The findings of this study highlight the role of perceived social support, sense of coherence and maternal-fetal attachment in contributing to expecting mothers’ mental health and well-being in urban India. These findings have implications for clinical practice and research, in tending to the subjective experiences of pregnant women to improve antenatal mental health. Future research investigating these psychosocial factors using longitudinal designs is warranted and would help clinicians and practitioners identify women at risk for perinatal mental health concerns.